A Passion for Cooperation Adventures of a Wide-Ranging Scientist - Axelrod, Robert (Campus Voices: Stories of Excellence from the University of Michigan, 2023)
A Passion for Cooperation is the exciting autobiography of Robert Axelrod, one of the most acclaimed and wide-ranging scientists of the last fifty years. After being recognized by President Kennedy for being a promising young scientist while in high school, Axelrod built a career dedicated to collaborating with business school professors, international relations scholars, political scientists, computer scientists, and even evolutionary biologists and cancer researchers. Fifty years later, he was honored by President Obama with the National Medal of Science for scientific achievement and leadership and his work has been referred to as the gold standard of interdisciplinary research. Yet Axelrod's autobiography is not just an account of his wide-ranging passion for cooperation. It reveals his struggles to overcome failures and experience the joys of gaining new insights into how to achieve cooperation. A Passion for Cooperation recounts Robert Axelrod's adventures talking with the leader of the organization Hamas, the Prime Minister of Israel, and the Foreign Minister of Syria. Axelrod also shares stories of being hosted in Kazakhstan by senior Soviet retired generals and visiting China with well-connected policy advisors on issues of military aspects of cyber conflict. Through stories of the difficulties and rewards of interdisciplinary collaborations, readers will discover how Axelrod's academic and practical work have enriched each other and demonstrated that opportunities for cooperation are much greater than generally thought.